A comparison of HFrEF vs HFpEF's clinical workload and cost in the first year following hospitalization and enrollment in a disease management program. (1st April 2017) - Murphy, T.M.; Waterhouse, D.F.; James, S.; Casey, C.; Fitzgerald, E.; O'Connell, E.; Watson, C.; Gallagher, J.; Ledwidge, M.; McDonald, K.
Abstract: Background: Admission with heart failure (HF) is a milestone in the progression of the disease, often resulting in higher intensity medical care and ensuing readmissions. Whilst there is evidence supporting enrolling patients in a heart failure disease management program (HF-DMP), not all reported HF-DMPs have systematically enrolled patients with HF with preserved ejection fraction (HFpEF) and there is a scarcity of literature differentiating costs based on HF-phenotype. Methods: 1292 consenting, consecutive patients admitted with a primary diagnosis of HF were enrolled in a hospital based HF-DMP and categorized as HFpEF (EF ≥ 45%) or HFrEF (EF < 45%). Hospitalizations, primary care, medications, and DMP workload with associated costs were evaluated assessing DMP clinic-visits, telephonic contact, medication changes over 1 year using a mixture of casemix and micro-costing techniques. Results: The total average annual cost per patient was marginally higher in patients with HFrEF €13, 011 (12, 011, 14, 078) than HFpEF, €12, 206 (11, 009, 13, 518). However, emergency non-cardiovascular admission rates and average cost per patient were higher in the HFpEF vs HFrEF group (0.46 vs 0.31 per patient/12 months) & €655 (318, 1073) vs €584 (396, 812). In the first 3 months of the outpatient HF-DMP the HFrEF population cost more on average €791 (764, 819) vs €693 (660, 728). Conclusion: There are greater short-term (3-month) costs of HFrEF versus HFpEF as part of a HF-DMP following an admission. However, long-term (3–12 month) costs of HFpEF are greater because of higher non-cardiovascular rehospitalisations. As HFpEF becomes the dominant form of HF, more work is required in HF-DMPs to address prevention of non-cardiovascular rehospitalisations and to integrate hospital based HF-DMPs into primary healthcare structures.